2011
DOI: 10.1007/s00270-011-0207-x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment in Emergency Setting of Acute Arterial Injuries After Orthopedic Surgery

Abstract: Percutaneous treatment is a feasible and safe tool for treating arterial injuries because it can provide fast and definitive resolution of the damage. This low-invasiveness approach can be proposed as first-line treatment in patients with acute injuries after orthopedic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Despite limited data on other IR procedures such as bronchial artery embolization for hemoptysis (Panda et al, 2017), CT-guided drainage of mediastinal abscesses (Arellano et al, 2011), and emergency treatment of arterial injury following orthopedic surgery (Carrafiello et al, 2012), high success rates have been reported. Moreover, reduced complications have been demonstrated for catheter-directed thrombolysis for pulmonary embolism (PE) versus anticoagulation alone (Bloomer et al, 2017).…”
Section: Interventional Radiologymentioning
confidence: 99%
“…Despite limited data on other IR procedures such as bronchial artery embolization for hemoptysis (Panda et al, 2017), CT-guided drainage of mediastinal abscesses (Arellano et al, 2011), and emergency treatment of arterial injury following orthopedic surgery (Carrafiello et al, 2012), high success rates have been reported. Moreover, reduced complications have been demonstrated for catheter-directed thrombolysis for pulmonary embolism (PE) versus anticoagulation alone (Bloomer et al, 2017).…”
Section: Interventional Radiologymentioning
confidence: 99%